Ag/n-GaAs schottky mis diodes with surface insulating layers prepared using (NH4)2S solutions without water - (:unkn) unknown (My University, 1998)
A study of the Schottky barrier height (SBH) and the ideality factor n was made using results of the temperature dependence of the experimental forward and reverse bias current-voltage (I-V) characteristics of Ag/n-GaAs MIS diodes. The diodes were fabricated on n-GaAs substrates utilizing insulating layers formed with dipping and anodic sulfidization methods. The sulfide-insulating layer was obtained using a (NH4)2S solution with propylene glycol, but without water. The Ag/n-GaAs MIS diode with a sulfide-insulating layer was found to cause a variation in Schottky barrier height (0.66 eV). The role of the sulfide-treatment or the sulfide layer on the GaAs surface in modifying the SBDs is most likely in the increase of interface stability of the treated surface which retards interfacial reactions between metal and semiconductor. © 1998 Elsevier Science Ltd.